On the Structure of Wealth-holding in Pre-Famine Ireland - Neil Cummins; Cormac Ó Gráda (University College Dublin, UCD Centre for Economic Research, 2020)
Very little is known about wealth-holding and its distribution in Ireland in the past. Here we employ death duty register data to analyse and identify a sample of the top wealth holders in Ireland between the early 1820s and late 1830s. We examine the sources of their wealth and its regional spread, and compare them with their British counterparts. We also discuss the share of Catholics and Quakers among top wealth-holders.
Keywords: N13; D31; 330; inequality; wealth; Ireland